2020
DOI: 10.3389/fphys.2020.543727
|View full text |Cite
|
Sign up to set email alerts
|

Selective Phosphodiesterase 1 Inhibitor BTTQ Reduces Blood Pressure in Spontaneously Hypertensive and Dahl Salt Sensitive Rats: Role of Peripheral Vasodilation

Abstract: Regulation of the peripheral vascular resistance via modulating the vessel diameter has been considered as a main determinant of the arterial blood pressure. Phosphodiesterase enzymes (PDE1-11) hydrolyse cyclic nucleotides, which are key players controlling the vessel diameter and, thus, peripheral resistance. Here, we have tested and reported the effects of a novel selective PDE1 inhibitor (BTTQ) on the cardiovascular system. Normal Sprague Dawley, spontaneously hypertensive (SHR), and Dahl salt-sensitive rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…The observed improvement in vascular function is independent of blood pressure-lowering effects, as we have previously shown that systolic and diastolic blood pressure lowering by the Ang II type 1 receptor antagonist losartan, did not improve vascular aging features in the Ercc1 Δ/model (Wu et al, 2017). Similar to our present study it was recently shown in hypertensive Dahl salt-sensitive rats on 4% NaCl chow that another selective PDE1 inhibiter (BTTQ) has an antihypertensive effect, both acutely as well as chronically (Dey et al, 2020). In these rats, a vasodilator response of isolated, preconstricted mesenteric arteries to BTTQ was observed in Dahl SS rats on 0.4 % NaCl.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The observed improvement in vascular function is independent of blood pressure-lowering effects, as we have previously shown that systolic and diastolic blood pressure lowering by the Ang II type 1 receptor antagonist losartan, did not improve vascular aging features in the Ercc1 Δ/model (Wu et al, 2017). Similar to our present study it was recently shown in hypertensive Dahl salt-sensitive rats on 4% NaCl chow that another selective PDE1 inhibiter (BTTQ) has an antihypertensive effect, both acutely as well as chronically (Dey et al, 2020). In these rats, a vasodilator response of isolated, preconstricted mesenteric arteries to BTTQ was observed in Dahl SS rats on 0.4 % NaCl.…”
Section: Discussionsupporting
confidence: 89%
“…It is highly expressed in the smooth muscle cell, and appears to contribute to the lack of vasodilation capacity in Ercc1 ∆/arteries, as demonstrated with the non-selective PDE inhibitor vinpocetine (Bautista et al, 2015). The potentially important role of PDE1 in vascular function and its correlation with several risk factors in cardiovascular diseases, including heart pressure-overload, hypertrophy, pulmonary arterial hypertension (PAH), and post-myocardial infarction, has been highlighted in several key studies (Fiona et al, 2007;Miller et al, 2009;Miller et al, 2011;Hashimoto et al, 2018;Dey et al, 2020).…”
Section: Introductionmentioning
confidence: 99%